PENGARUH PROGRESSIVE MUSCLE RELAXATIONS TERHADAP KUALITAS TIDUR DAN KADAR GULA DARAH PADA DIABETES DI DESA HULU KECAMATAN PANCUR BATU KABUPATEN DELI SERDANG - Magda Siringo-ringo; Imelda Sirait; Lindawati Simorangkir (Program Studi S1/DIII-Keperawatan Universitas Imelda Medan, 2021)
Diabetes erupts relatively resulting in a mechanism for controling glucose levels in the body, if it is not controlled creates potential complications of experiencing hyperglycemia and hyperglycemia. Condition can be found in diabeteic patients experiencing anxiety, prolonged severe stress and lack of activity/exercise, resulting in inadequate sleep quality, eventually leading to increased blood glucose levels in every system of the body. The research design was quasi experimental method with pre and post with control group, for each group consisted of 32 samples with consecutive sampling technique. The data were analyzed statistically by Wilcoxon Sign Range Test and Mann Whitney U. The result showed that there was an effect of progressive muscle relaxation with a very significant increase in sleep quality where the first intervention difference was (1) in diabetes p = 0.695 (<0.05), and the second intervention group (2) p= 0.00 (p<0.05), with the second group intervention (2) diabetes p= 0.00 (p<0.05). Suggestions to diabetic patients always try actively perform progressive muscle relaxation regularly and measurably every day, in reducing muscle tension, stress anxiety stabilize blood glucose levels and improve sleep quality in the pillars of controlling diabetes complications.